Synthesis of Pyridiniumboranephosphonate Diesters and Related Compounds using Trityl Cation as a Borane Hydride Acceptor - Rachwalak, Marta; Gołębiewska, Justyna; Jakubowski, Tomasz; Stawinski, Jacek (Synthesis, 2020)
Boranephosphonate diesters react with pyridine and some tertiary amines in the presence of dimethoxytrityl chloride used as a borane hydride acceptor, to afford the boron-modified phosphodiester analogues containing a P-B-N structural motif. The reaction provides a convenient entry to pyridinium- and ammoniumboranephosphonates derived from the corresponding alkyl, aryl, or nucleoside boranephosphonate diesters. Some aspects of the synthetic protocol, mechanistic features related to a possible intermediate involved, and the role of the solvents used, are discussed.
Keywords: H-phosphonates; boranephosphonates; pyridiniumboranephosphonates; trityl cation; nucleotide analogues